How is entrepreneurship as generic and professional competences diverse? Some reflections on the evaluations of university students' generic competences (students of education and bioeconomics) - Slišāne, Agnese; Lāma, Gatis; Rubene, Zanda (Frontiers in Education, 2022)
Generic competence has an interdisciplinary nature, which indicates its usability in different disciplines, situations, and contexts in the performance of different tasks. Generic competences are thus considered from two perspectives – daily life and professional activity – that are equally important, meaning that generic competences are necessary for individuals to successfully adapt to change and live meaningful and productive lives. Entrepreneurship competence can be observed from two perspectives: as a generic competence viewed from the perspective of the individual’s personal experience and as a professional competence viewed from the perspective of the individual’s professional experience. In this article, it will be observed from both perspectives in order to see its performance in diverse contexts and to clarify distinctions between these contexts. The aim of the study is to shed light on how specific university study disciplines with a professional focus (educational sciences and bioeconomics) support the development of a specific generic competence (entrepreneurship competence). The specific research questions of this article are: 1. What is the self-assessment of entrepreneurship competence of Latvian bioeconomy and education students? 2. What are the differences in the self-assessment of entrepreneurship competence of Latvian bioeconomy and education students?(Does the professional field influence the self-assessment of students' entrepreneurial competence?? 3. What are the main correlations between the students’ self-assessed areas of entrepreneurship competence? Data for the study was gathered by using the online survey platform QuestionPro. The questionnaire was filled in by 135 students, of whom 82 were from educational sciences and 53 from the field of bioeconomics. The study presents a comparison of entrepreneurship competence self-assessments of bachelor’s, master’s, and doctoral students of bioeconomics and educational sciences. Despite the fact that entrepreneurship is more linked to economics, the results show that in two out of three main areas of entrepreneurship competence, students of educational sciences self-assessed their entrepreneurship competences higher than students of bioeconomics.